Pentoxifylline adjunct to risperidone for negative symptoms of stable schizophrenia: a randomized, double-blind, placebo-controlled trial - Shamabadi, Ahmad; Rafiei-Tabatabaei, Elham-Sadat; Kazemzadeh, Kimia; Farahmand, Kimia; Fallahpour, Bita; Khodaei Ardakani, Mohammad-Reza; Akhondzadeh, Shahin (The international journal of neuropsychopharmacology, 2025)
Abstract Background Negative symptoms of schizophrenia represent an unmet therapeutic need for many patients in whom pentoxifylline may be effective in terms of its dopaminergic, anti-inflammatory, and cerebral blood flow–increasing properties. This study aimed to evaluate pentoxifylline as a therapeutic agent for improving negative symptoms of schizophrenia. Methods Chronic schizophrenia outpatients experiencing significant negative symptoms were randomly allocated to receive pentoxifylline 400 mg or matched placebo every 12 hours for 8 weeks. All patients were clinically stable as they had received risperidone for at least 2 months, which was continued. The participants were assessed using the Positive and Negative Syndrome Scale (PANSS), Hamilton Depression Rating Scale, Extrapyramidal Symptom Rating Scale, and side effect checklist. Results The patients’ baseline characteristics were comparable between the groups. There was a significant time–treatment interaction effect on PANSS negative subscale scores (ηP2=0.075), with the pentoxifylline group showing significantly greater reductions until weeks 4 (Cohen d = 0.512) and 8 (Cohen d = 0.622). Also, this group showed a significantly better response by week 8. Other PANSS scores, Hamilton Depression Rating Scale scores, Extrapyramidal Symptom Rating Scale scores, and side effect frequencies were comparable between the groups. Pentoxifylline showed a nonsignificant higher remission of 37.1% compared with 14.7% in the placebo group. Conclusions Pentoxifylline was safely and tolerably beneficial for the primary negative symptoms of chronic schizophrenia.